Academic Problems among Students with SLD and its Relationship to Teachers’ Attitudes toward the Use of Assistive Technologies - Hemedan, Nabil Salah; Joudeh, Iman; Joudeh, Noura (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the academic problems among students with SLD and its relationship to teacher’s attitudes towards the use of assistive technologies in Amman. To achieve the objectives of the study, the researcher followed the correlative descriptive approach by developing two tools, the scale of teacher’s attitudes towards the use of supportive techniques, and the scale for estimating academic problems. A simple random sample of the respondents was drawn (44%) of the study population of (250) teachers, and thus the volume of The study sample is (110) male and female teachers in the learning resource rooms in public and private schools for the academic year (20/21), and the study reached a set of results, the most prominent of which were: The level of teacher’s attitudes towards the use of supportive technologies in teaching came with an arithmetic average of (3.30) and at an average rating level, The results showed that the level of academic problems of students with SLD (reading, writing, and arithmetic) was generally average depending on their total arithmetic mean, which amounted to (3.61), and the results also showed a correlation between teachers’ attitudes towards using supportive techniques and reducing academic problems. For students with SLD. The study recommended the necessity of holding workshops and specialized training programs for teachers of learning resource rooms in order to increase their efficiency in dealing with various supportive technology tools to make the most of the advantages.